Retrospective cohort analysis of pediatric daycare anesthesia in dentistry: An assessment of postoperative complications: Complications in pediatric daycare anesthesia in dentistry - Orbay Yaşlı, Seher; Günay Canpolat , Dilek; Baydan, Ebru (Journal of Surgery and Medicine, 2023)
Background/Aim: In pediatric populations, the frequent challenges of patient cooperation often necessitate treatments to be performed under general anesthesia. Since these procedures do not fall under the category of major surgery, daycare anesthesia has become a prevalent approach in this field. The advantages of daycare anesthesia, such as reduced hospital stay durations and costs, make it a preferred method. It is well-recognized that daycare anesthesia, when applied across various surgical fields, has unique postoperative complications, which can sometimes be linked to the surgical procedure itself. Dental treatments represent a specific surgical domain, and elucidating potential postoperative complications in this area draws attention to preventive measures and is vital for enhancing postoperative patient comfort. The primary objective of this study was to evaluate and identify the most prevalent postoperative symptoms and complications associated with pediatric dentistry. Methods: This retrospective cohort study was conducted at the Erciyes University Faculty of Dentistry between January 15 and April 15, 2019. We analyzed records of 245 pediatric patients aged 3 to 13 who underwent day-case dental procedures. The inclusion criteria encompassed all patients who underwent dental procedures under general anesthesia and were classified as ASA 1-2. Variables such as demographic data, procedure duration, comorbidities, and postoperative complications were extracted and analyzed for the current study. Results: Out of the 245 pediatric patients, the median age was 6.0 years, ranging from 3.0 to 13.0 years. Females comprised 52.7% of the cohort. Most patients (62.9%) were classified under ASA class one. 27.8% of the patients reported postoperative complications such as sore throat, hoarseness, cough, or nausea/vomiting. The most prevalent postoperative complications were hoarseness (11.4%) and sore throat (9.8%). Demographic and clinical characteristics of patients with and without postoperative complications were compared. Gender significantly influences the occurrence of postoperative complications. Males had a rate of 11.0% (27 out of 245), while females had a rate of 16.7% (41 out of 245), with females experiencing complications at a higher rate than males (P=0.01). Age also played a role in complications: the mean age for patients with complications was 6.0 years, compared to 5.0 years for those without complications (P=0.02). Conclusion: Pediatric daycare anesthesia, especially for dental procedures, has proven effective and safe. However, each child presents a unique set of challenges, and it’s crucial to recognize and mitigate potential risks. By understanding common postoperative symptoms and tailoring anesthesia techniques accordingly, healthcare professionals can optimize outcomes and enhance the quality of pediatric patient care.